Sustainable biorefining of woody biomass to biofuels and biochemicals - Kumar, Deepak; Kumar, Sachin; Rajendran, Karthik (Woodhead Publishing, Elsevier, 2024)
Sustainable Biorefining of Woody Biomass to Biofuels and Biochemicals explores various technologies and pathways for the valorization of woody biomass to produce sustainable biofuels and bioproducts. Focusing on commercialization, the book discusses woody biomass availability, including harvesting, transportation and storage, biomass structure, advanced biorefinery technologies, and the economic and environmental sustainability of woody biomass-based biorefineries. Various technologies are described and assessed from a commercial perspective and practical solutions to the latest challenges are provided. The last section of the book is dedicated to the commercialization aspects of biorefineries, providing details about the techno-economic viability and environmental impact of various biorefinery approaches.This book provides readers with a unique and comprehensive reference that will help students and researchers alike identify and overcome the challenges involved in woody-biomass biorefining for biofuels and biochemicals. It will also be of interest to researchers and professionals involved more broadly in bioenergy and renewable energy, and interdisciplinary teams working across biotechnology, chemistry and chemical engineering, environmental science, and plant sciences
1. Structure and chemistry of woody biomass2. Woody biomass availability, supply chains and logistics3. Pretreatment strategies for woody biomass4. Biochemical conversion of woody biomass to liquid biofuels5. Utilization of woody biomass for biogas production6. Thermochemical conversion of woody biomass to energy and high-value products7. Sustainable production of advanced biofuel and platform chemicals from woody biomass8. Downstream recovery of products and coproducts from bioprocessing of woody biomass9. Hot-water extraction based biorefinery for woody biomass10. Lignin based novel bioproducts from woody biomass11. Carbon capture and circular economy of woody biomass12. Techno-economic assessment of wood biomass to biofuels and bio-products13. Environmental impact assessment of utilizing woody biomass to biofuel and bio-products14. Commercializing Biorefinery Technology: choice of selecting various product pathways15. Policies and regulation on commercializing woody biomass-based biofuels and products
Keywords: Aufsatzsammlung